InDesign CS 6: For windows and macintosh - Cohen, Sandee (Peachpit Press, 2013)
InDesign CC: Visual QuickStart Guide is your complete guide to the core functions of InDesign as well as all the important new features. New to this edition is author Sandee Cohens brilliant inclusion of scannable QR codes providing readers with a service that connects you via the Internet directly and conveniently to specifically created video lessons. These videos and tutorials allow you to hear and see Sandee explain InDesigns powerful capabilities clearly and completely. They enhance and enrich the experience taking your learning to a whole new level. Complete coverage of InDesign CC's new features includes: updated tools for a variety of output formats; the new QR code generator, to easily allow linking to online content; and Font Favorites, to make it easy to customize workspaces. Users will learn how to create and automate documents, import and style text and objects, manage long documents, export files for a wide variety of purposes, and much more.